IMPLEMENTASI PENDEKATAN PEMBELAJARAN CULTURAL RESPONSIVE TEACHING (CRT) BAGI ABK MATERI SENAM IRAMA - Khoirun Najib, Muhammad (Journal of Physical Activity and Sports (JPAS), 2024)
This study aims to determine the implementation of the Cultural Responsive Thinking learning approach for ABK rhythmic gymnastics material (poco-poco) at SMPN 37 Semarang. The research method used is descriptive qualitative with the subject of physical education teachers and the object of ABK. Data collection was carried out in three stages, namely interviews, observation, and documentation. The results of this study indicate that the learning of Cultural Responsive Thinking rhythmic gymnastics material (poco-poco) especially for Students with special needs can run smoothly. Students with special needs can participate in learning both classically and in groups. Some students with special needs still have a low level of thinking which has an impact on the ability to grasp poco-poco gymnastics movements which are still lacking. So that with this, teachers can be more creative and innovative in creating learning methods and approaches so that all students can understand the material being taught. The conclusion of the implementation of the Cultural Responsive Thinking approach for students with special needs in rhythmic gymnastics (poco-poco) material for class 7 of SMPN 37 Semarang in the 2024/2025 academic year is that students with special needs can participate in learning by imitating the poco-poco gymnastics movements of friends and teachers.